CHANCE AND DESIRE, THE ROOT OF CONSTRUCTION CLAIMS - Sarwono Hardjomuljadi (Universitas Muhammadiyah Jakarta, 2011)
In a construction project contract activities, can certainly be differences of opinion over theinterpretation of contract clauses that develop into disputes. In the event of any dispute, anyparty that ultimately wins through the process ofarbitration or litigation, the loss will always be in the service user.Differences of opinion, where one side feels the contractor services provider mustsubmit a claim to be eligible fordoing something or because they feel harmed by the behavior ofthe service users, all while the service users do notfeel obligated to pay because they do not feel or not feel commanded complicate or lead to the existence ofbarriers to the contractor.Pre-contract strategy from the service user, which is preparing a general conditions of contract which has beenstandardized as FIDIC General Conditions of Contract, known as a fair and balanced conditions that canbe done to reduce the possibility offiling a claim from the contractor that occurs because ofthe